Determinants of corporate cash holding: evidence from UK listed firms - Le, Duac Hoang; Tran, Phi Long; Ta, Thu Phuong (Business and economic horizons, 2018)
Our paper revisits the determinants of company cash holding. It attempts to explain the cash holding behavior of firms’ managers by investigating non-financial companies listed on the London Stock Exchange from 2011 to 2016. Our results indicate that firm size, leverage, cash flow, cash flow volatility, and investment opportunity exert influence on such cash holding behavior. It can be explained by the trade-off theory, the pecking-order theory and free cash flow theory. Our results may shed light on the decrease in the cash holding level for the post-crisis period.